2009
DOI: 10.1089/pho.2008.2383
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 660 nm and 780 nm Laser Irradiation on Viability of Random Skin Flap in Rats

Abstract: This present study showed that 660 nm and 780 nm lasers at doses of 30 and 40 J/cm(2) were not effective for decreasing the necrotic area of the skin flaps in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
0
14
0
8
Order By: Relevance
“…The mostly feared of these events is skin flap necrosis, caused by inadequate blood flow [1–4]. Under ideal conditions, hypoxia resulting from improper tissue perfusion should lead to an adaptive response, inducing angiogenesis, that is, the formation of new vessels from pre-existing ones, a necessary step to ensure adequate blood supply during the healing process [5–7].…”
Section: Introductionmentioning
confidence: 99%
“…The mostly feared of these events is skin flap necrosis, caused by inadequate blood flow [1–4]. Under ideal conditions, hypoxia resulting from improper tissue perfusion should lead to an adaptive response, inducing angiogenesis, that is, the formation of new vessels from pre-existing ones, a necessary step to ensure adequate blood supply during the healing process [5–7].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the results reported by Cury et al (13), it may be suggested that the lack of influence of laser irradiation on the viability of skin flaps occurred due to the correlation of the distance between the irradiated points and the energetic magnitude irradiated in each point. Additionally, Cury et al (13) took advantage of a significantly higher number of suture points than those used in the surgical technique performed in other studies, which could have led to more tension on the flap and possible complications to the local microcirculation.…”
Section: Discussionmentioning
confidence: 91%
“…All of these factors may be associated with increased viability of skin flaps. However, some studies have shown that LLLT was not effective at improving the viability of random skin flaps in rats (3,13).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effects of low-level laser therapy on the viability of skin flaps [4,[7][8][9][29][30][31][32][33][34][35][36]. Wavelengths in the visible red light spectrum (632.8, 660 and 670 nm) [7,29,[31][32][33][34][35][36] and infrared spectrum (780 and 830 nm) [4,8,9,34,36] are the most commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…Wavelengths in the visible red light spectrum (632.8, 660 and 670 nm) [7,29,[31][32][33][34][35][36] and infrared spectrum (780 and 830 nm) [4,8,9,34,36] are the most commonly used. However, all the above-mentioned studies used different dosimetric parameters in the formulation of applied doses.…”
Section: Discussionmentioning
confidence: 99%